The relationship between board’s diversity and the reputation of integrated reports - Braz, M. J. O.; Lopes, A. I. (XVIII Encontro Internacional AECA, 2018)
The integrated reporting arises as an answer to the insufficiency of traditional financial report and the emergent need to disclose non-financial information to stakeholders, and it is proposed by the International Integrated Reporting Council. Given the influence of corporate governance on corporate disclosure and the key role of the companies’ board of directors in managing the disclosure of a wide range of information, the present study aims to analyze how some corporate governance characteristics may influence the reputation of integrated reports, distinguishing between reference reports and regular reports. The sample of this study comprises 374 reporters extracted from the IIRC Examples Database. The results show that the size and the experience of the board of directors does not influence the reputation of the integrated reports. In turn, the independence of the board and gender diversity influence positively the reputation of integrated reports, while role duality seems to influence negatively.